Peningkatan Kualitas Pelayanan Publik pada Dinas Kependudukan dan Catatan Sipil Kota Bandung Berdasarkan Survei Kepuasan Masyarakat - Rangkuti, Sarah Asrina; Kurniawan, Iwan (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2022)
Improving the quality of public services is the responsibility of the government toward stakeholders to create an effective, efficient, and accountable service product. The purpose of this study was to determine the implementation of public services in The Population and Civil Registration Agency (Dinas Kependudukan dan Catatan Sipil – Disdukcapil) of Bandung City, measure the level of public satisfaction with the quality of public services and provide suggestions to improve the quality of public services in the Disdukcapil Bandung. The research method used is a mixed approach /methods with questionnaires, interviews, and documentation studyies as data collection techniques and accidental sampling as sampling technique. Data was analysed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) for quantitative approach, and qualitatively using Miles and Huberman. The results showed that the quality of public services on public satisfaction in Disdukcapil Bandung was good. This study gave suggestion to improve three aspects, i.e. service time, human resource competency, and the management of complaint handling. The study proposed Disdukcapil to create an integrated one-stop service to overcome the massive queues, that often occur and gave intensive training to improve human resources quality, especially in the service department.